PENGEMBANGAN BUKU PANDUAN PERMAINAN TRADISIONAL SETATAK DALAM PEMBELAJARAN MATEMATIKA KELAS III SD - Sitanggang, Nova Jessica; Syahrilfuddin, Syahrilfuddin; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Absctract: The background of this research is the llack of teacher reference sources in the form of a guidebook to teach mathematics by using “setatak” games. This research aims to: (1) describe the procedures of Analyis, Design, Development, Implementation, Evaluation in development of traditional game guide books “setatak” on third (3) class in junior high school in mathematics learning and (2) find out the feasibility of the guidebook. The results of the validation carried out by the four validators obtained an average value 4,6 with a very good category. Form the results of product trials by the teacher it was found that the teacher understood and could practice learning using traditional games “setatak”, this book is accordance wtih the ten indicators of the guidebook, besides that te teacher feels confident in teaching using traditional games. Meanwhile form the results of the game trials it was found that there were twenty three student felt happy and easily understood the learning of mathematics with games “setatak”.Key Words: Guidebook, Game “setatak”, Mathematics.